Pengaruh metode latihan terhadap peningkatan hasil pukulan forehand dan backhand tenis lapangan - Budi, Didik Rilastiyo; Syafei, Muhammad; Kusuma, Moh. Nanang Himawan; Suhartoyo, Topo; Hidayat, Rohman; Listiandi, Arfin Deri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2020)
Tennis is a sport that has a high level of skill complexity. Therefore, increasing mastery of punch techniques especially the forehand groundstroke and the backhand groundstroke techniques is essential. The purpose of this study is to examine the level of forehand and backhand groundstroke skills of students of Physical Education, Sport, Health and Recreation (PJKR) department, Health science Faculty, Jenderal Sudirman University (UNSOED), using block and random practice training method. Research employs experimental methods. The research sample is 2017 class male students of PJKR FIKES UNSOED using the purposive random sampling technique. The research instrument employs Dyer Tennis Test, with a validity of 0.85 and a reliability of 0.90. Moreover, data analysis uses a prerequisite test consisting of normality and homogeneity tests and hypothesis testing applies t test with a significance of 0.05. The results is random practice method has better effect compared to block practice method in improving the students forehand groundstroke and backhand groundstroke technical skills.